Evidence for inequalities in the management of coronary heart disease in Scotland. (14th April 2005) - Simpson, C R; Hannaford, P C; Williams, D
Abstract : Objectives: To investigate whether sex, age, and deprivation inequalities existed in the prescription of secondary preventive treatment for coronary heart disease (CHD) in Scottish general practice and whether these differences altered over time. Design: 6 year cross sectional study based on general practice morbidity and prescribing data. Setting: 55 primary care practices in Scotland. Subjects: 14 435 patients with diagnosed CHD. Main outcome measure: Prescription of various groups of secondary preventive treatment in six study years. Results: The use of all secondary prevention treatments increased over time (63.6% of patients with CHD in 1997 to 87.6% in 2002). After adjustments for age, sex, deprivation, co-morbidities, and practice where appropriate, women received fewer secondary prevention treatments than men, a difference that increased over time (March 1997: adjusted odds ratio (OR) 0.9, 95% confidence interval (CI) 0.8 to 1.0; March 2002: OR 0.6, 95% CI 0.6 to 0.7). Sex differences were observed within each group of treatments studied. The oldest group of patients was less likely than the youngest group to receive any secondary preventive treatment in the year up to March 1997 (OR 0.6, 95% CI 0.5 to 0.7) but were more likely by 2002 (OR 1.3, 95% CI 1.1 to 1.5) to receive secondary prevention. The most affluent patients with CHD were significantly less likely to receive a statin between March 1998 and 2001 (March 1998 OR 0.6, 95% CI 0.5 to 0.9), a finding that disappeared by 2002 (OR 0.9, 95% CI 0.7 to 1.1). Conclusion: The results suggest that inequalities exist in the secondary prevention of CHD in Scotland.